Utilization and impact of electronic and print media on the patients’ health status: physicians’ perspectives - Shakeel, Sadia; Nesar, Shagufta; Rahim, Najia; Iffat, Wajiha; Ahmed, Hafiza Fouzia; Rizvi, Mehwish; Jamshed, Shazia Qasim (Medknow Publications, 2017)
Aims: Despite an increased popularity of print and electronic media applications, there is a paucity of data reflecting doctors’ opinions regarding efficient utilization of these resources for the betterment of public health. Hence, this study aimed to investigate the perception of physicians toward the effect of electronic and print media on the health status of patients. Setting and Design: The current research is a cross-sectional study conducted from January 2015 to July 2015. The study population comprised physicians rendering their services in different hospitals of Karachi, Pakistan, selected by the nonprobability convenience sampling technique. In this study, 500 questionnaires were distributed through email or direct correspondence. Methods and Materials: Physicians’ perception toward the impact of electronic and print media on the health status of patients was assessed with a 20-item questionnaire. Different demographic characteristics, such as age, gender, institution, position, and experience of respondents, were recorded. Quantitative data were analyzed with the use of Statistical Package for Social Sciences, version 20.0 (SPSS, Chicago, IL). The association of the demographic characteristics of the responses of physicians was determined by one-way ANOVA using 0.05 level of significance. Results: In this study, 254 physicians provided consent to show their responses for research purposes. A response rate of 50.8% was obtained. Nearly one-third of the respondents negated that patients get health benefit using electronic and print media. The majority did not consider electronic and print media as lifestyle-modifying factors. Physicians thought that patients particularly do not rely on mass media for acquiring health information and consider healthcare professionals as unswerving information resource. Conclusions: Mass media can be productive resources to augment awareness among patients, although physicians seem unconvinced about the extended usage of print/electronic media.